2018
DOI: 10.4014/jmb.1804.04025
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Activity against Dirty Panicle Rice Fungal Pathogens and Plant Growth-Promoting Activity of Bacillus amyloliquefaciens BAS23

Abstract: Bacterial strain BAS23 was isolated from rice field soil and identified as Bacillus amyloliquefaciens. Based on dual culture method results, the bacterium BAS23 exhibited potent in vitro inhibitory activity on mycelial growth against a broad range of dirty panicle fungal pathogens of rice (Curvularia lunata, Fusarium semitectum and Helminthosporium oryzae). Cellfree culture of BAS23 displayed a significant effect on germ tube elongation and mycelial growth. The highest dry weight reduction (%) values of C. lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Biological control agents viz. Trichoderma, Talaromyces, and Bacillus against this disease have been reported in Thailand 6,26,29 . In the current study, the combined fungicides of triazole and fluopyram + tebuconazole demonstrated dirty panicle disease suppression of up to 60% when applied twice, while two applications of the strobilurin fungicide, azoxystrobin, reduced the incidence of the disease by 56% in 2016, a year of heavy rainfall.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Biological control agents viz. Trichoderma, Talaromyces, and Bacillus against this disease have been reported in Thailand 6,26,29 . In the current study, the combined fungicides of triazole and fluopyram + tebuconazole demonstrated dirty panicle disease suppression of up to 60% when applied twice, while two applications of the strobilurin fungicide, azoxystrobin, reduced the incidence of the disease by 56% in 2016, a year of heavy rainfall.…”
Section: Discussionmentioning
confidence: 98%
“…Mancozeb is an effective fungicide which carries out the protective activity of inhibiting spore germination but only on leaf surfaces 27 . Rainfall may have lowered mancozeb's fungicidal activity against rice diseases in field trials 28,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection is done using techniques such as liquid chromatography–mass spectrometry (LC–MS). Examples of these studies are those which were conducted to detect and/or analyze surfactin, fengycin, and iturin produced by Bacillus against various plant pathogenic fungi [77,100,101,102,103,104,105,106,107]. Two initial scenarios may require this type of testing.…”
Section: Techniques Applied To Establish Potential Modes Of Actionmentioning
confidence: 99%
“…Bacteria are another important component of the plant root microbiome that plays a key role in plant nutrition, root development and plant health. Some bacterial strains enhance nutrient acquisition in plants (Nissinen et al, 2012;Bulgarelli et al, 2013;Vandenkoornhuyse et al, 2015;Kielak et al, 2016), support stress adaptation (Vandenkoornhuyse et al, 2015) or, like Bacillus amyloliquefaciens, suppress plant pathogens (Santhanam et al, 2015;Gómez Expósito et al, 2017;Saechow et al, 2018). Others can have deleterious or no visible effects on plants (Mansfield et al, 2012).…”
Section: Introductionmentioning
confidence: 99%